2022
DOI: 10.3390/v14112540
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antiviral Treatment for COVID-19: A Comprehensive Review on Nirmatrelvir/Ritonavir

Abstract: Despite the rapid development of efficient and safe vaccines against COVID-19, the need to confine the pandemic and treat infected individuals on an outpatient basis has led to the approval of oral antiviral agents. Taking into account the viral kinetic pattern of SARS-CoV-2, it is of high importance to intervene at the early stages of the disease. A protease inhibitor called nirmatrelvir coupled with ritonavir (NMV/r), which acts as a CYP3A inhibitor, delivered as an oral formulation, has shown much promise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 54 publications
0
47
0
1
Order By: Relevance
“…A recent literature review shows that a growing body of real-world evidence supports the efficacy of Paxlovid among vaccinated adult patients in the Omicron era [18], though most of those observational studies were conducted during the BA.1/BA.2 wave. A large-scale cohort study in Israel showed that among high-risk outpatients with COVID-19 aged ≥65 years, Paxlovid users had substantially lower risks of hospitalisation due to COVID-19 (adjusted hazard ratio=0.27, 95% CI: 0.15 to 0.49) and death due to COVID-19 (adjusted hazard ratio=0.21, 95% CI: 0.05 to 0.82) than untreated patients; whereas no association was observed in patients aged <65 years [5].…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature review shows that a growing body of real-world evidence supports the efficacy of Paxlovid among vaccinated adult patients in the Omicron era [18], though most of those observational studies were conducted during the BA.1/BA.2 wave. A large-scale cohort study in Israel showed that among high-risk outpatients with COVID-19 aged ≥65 years, Paxlovid users had substantially lower risks of hospitalisation due to COVID-19 (adjusted hazard ratio=0.27, 95% CI: 0.15 to 0.49) and death due to COVID-19 (adjusted hazard ratio=0.21, 95% CI: 0.05 to 0.82) than untreated patients; whereas no association was observed in patients aged <65 years [5].…”
Section: Findings In Contextmentioning
confidence: 99%
“…Another cohort study in the US population showed that non-hospitalised adult patients who were prescribed Paxlovid had a lower risk of all-cause hospitalisation or death than non-users (adjusted risk ratio=0.56, 95% CI: 0.42 to 0.75) [19]. The evidence for the safety of Paxovid in routine clinical use, however, is still limited, and the concerns of viral rebound and recurrence of COVID-19 symptoms following Paxlovid treatment need further investigation [18].…”
Section: Findings In Contextmentioning
confidence: 99%
“…Nirmatrelvir is a peptidomimetic inhibitor of the SARS-CoV-2 main protease that prevents viral replication, and ritonavir acts as a CYP3A4 inhibitor that enhances the bioavailability of nirmatrelvir. 8 The present emergency use authorization for nirmatrelvirritonavir is indicated for individuals with mild or moderate acute COVID-19, and high risk of severe infection. 9 However, it remains unclear whether the patient had COVID-19 re-infection with falsenegative testing, or whether the patient acquired a different viral infection that caused similar symptoms, and how this may have impacted the chronic PASC symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the orally active nirmatrelvir (PF-07321332) in combination with ritonavir, was granted emergency use by the FDA in December 2021 for COVID-19 treatment under the trade name Paxlovid ® 10 . The combination elicited an efficacy of about 88% against hospitalisation or mortality in adult outpatients after its administration within five days of the onset of symptoms 11 . Nirmatrelvir is a peptidomimetic inhibitor of the main protease Mpro that acts via a reversible covalent interaction with its key Cys-145 residue 12 .…”
Section: Introductionmentioning
confidence: 99%